Pengujian Efisiensi Pasar Bentuk Lemah di Bursa Saham Kuala Lumpur - D. Agus Harjito (Management Development Centre (MDC) Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2003)
The purpose of this study is to examine the weak-form of the efficient market hypothesis on the Kuala Lumpur Stock Exchange (KLSE). The weak form of the efficient market hypothesis asserts that the short-run future price movements of stock issue are approximately random in character: that is, there are independent of the past history of price movements. A market is efficient in the weak form sense if stock prices fully reflect the information implied by all past price movements. This study employ weekly closing prices of the 40 stocks selected from companies continuously listed on the second board of KLSE from the period July 1997 through December 2002. This period was separated into two sub-periods. The first sub-period is from July 1977 to December 1998 as the economic crisis period, and the second sub-period is from January 1999 to December 2002 as the post-crisis economic period. To examine the weak form efficient market hypothesis three models, i.e, serial correlations test, run test, and unit root test were used. The results showed that the weak form efficient market hypothesis is exhibited in the second board of Kuala Lumpur Stock Exchange during and after the economic crisis period as well.